Changes in Social Interaction in Elderly People with Chronic Diseases at the Muara Fajar Riau Community Health Center - Sirait, Ruminta (Jurnal EduHealth, 2023)
Abstract: Elderly or old age is a closing period in a person's life span, namely a period where a person has moved away from previous periods that were enjoyable, or moved away from times that were full of benefits. As age progresses, health problems begin to experience problems, especially chronic diseases. In this case, the emergence of chronic disease will affect the elderly in their social interactions with other people. This research aims to identify changes in the social interactions of elderly people with chronic diseases using a descriptive design, using purposive side as many as 43 respondents. Data was collected using a questionnaire. The data that has been collected is analyzed. From the results of the analysis it was obtained (88, 4%) of respondents experienced changes in social interactions or elderly social interactions were categorized as bad. The results of this study recommend that nurses improve nursing care for elderly people with chronic diseases regarding changes in their social interactions.